The dependency of the banks' assets and liabilities: evidence from Germany - Christoph Memmel; Andrea Schertler (Deutsche Bundesbank, 2009)
Developments in risk-transfer instruments and risk management techniques in the last two decades have fundamentally changed how banks manage their assets and liabilities. In this document we show that, for all three sectors of German universal banks (private commercial banks, savings banks, and cooperative banks), asset-liability dependency declined over the period 1994-2007, the decline was strongest for those banks that use more than sector-average amounts of derivatives. Only in the case of private commercial banks, we do find that lower regulatory capital has coincided with higher asset-liability dependencies. Over our sample period, the difference has diminished since poorly-capitalized private commercial banks have reduced their asset-liability dependencies more intensively than their well-capitalized counterparts. Moreover, we find that profitability matters for the asset-liability dependency but not in the same way for all three sectors. Asset-liability dependency is lower for private commercial banks with higher provision income, savings banks with lower ROE volatilities and cooperative banks with higher ROEs.
Keywords: G21; G32; 330; Asset-liability dependency; maturity; correlation analysis; Bank; Bilanzstrukturmanagement; Laufzeit; Finanzintermediär; Finanzderivat; Rentabilität; Risiko; Deutschland